234k views
4 votes
How can u write a mathematical proof to show that (x+a) (x+b) is equivalent to x2+ ax+bx +ab

1 Answer

3 votes

(x+a) * (x+b)

First off you have to solve whats in the parentheses

First Parentheses: x*x = x^2 Then : x*b = bx

I multiplied x times x which is x squared, then i multiplied x times b which equals bx

Second parentheses: a*x= ax , Then: a*b=ab

i multiplied a times x which is ax, then i multiplied a times b and that equals ab

so our answer is = x2+bx+ax+ab

Right here

All of this together

User Catalina Astengo
by
5.4k points